Analisis Sumber Penyebab Kesalahan Berbahasa Pada Konten Youtube Nadia Omara Dalam Meningkatkan Keterampilan Berbicara - Irfanda Siti Amaliyafitri; Diena San Fauziah (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research discusses the analysis of language errors based on their sources and causes. This research aims to determine the source and cause of language errors from Nadia Omara's YouTube content "Holy Tree KHW Part 203" and relate it to speaking skills. Using appropriate language can influence someone in improving their speaking skills. The method used is descriptive qualitative with data collection techniques using note-taking techniques. The results of this analysis show 3 sources and causes of language errors with several words.